Computer adaptive test performance in children with and without disabilities: prospective field study of the PEDI-CAT. - Dumas, Helene M.; Fragala-Pinkham, Maria A.; Haley, Stephen M.; Ni, Pengsheng; Coster, Wendy; Kramer, Jessica M.; Kao, Ying-Chia; Moed, Richard; Ludlow, Larry H. (Disability & Rehabilitation, 2012)
Purpose: To examine the discriminant validity, test-retest reliability, administration time and acceptability of the pediatric evaluation of disability inventory computer adaptive test (PEDI-CAT). Methods: A sample of 102 parents of children 3 through 20 years of age with ( n == 50) and without ( n == 52) disabilities was recruited for this prospective field study. A sub-sample ( n == 25) also completed the PEDI-CAT a second time within one month. Parents completed 15 items in each of the four PEDI-CAT domains (daily activities, mobility, social/cognitive, responsibility) using a laptop computer. Following completion, parents answered a four-question user evaluation survey. Results: PEDI-CAT scores based on parent responses differentiated between groups of children with and without disabilities in all four domains. Test-retest reliability estimates were high (ICC == 0.96-0.99) for all four domains. The mean time to complete 60 items for the full sample ( n == 102) was 12.66 minutes (SD == 4.47). Parents reported favorable reactions to the PEDI-CAT. Conclusions: The PEDI-CAT offers a valid and reliable assessment acceptable to parents.